Analysis Muslim Personality Formation Through Islamic Education: In Bibliometric Inquiry - Aprillia Haya, Alif Dhita; Azani, Mohammad Zakki; Apriantoro, Muhamad Subhi; Ikhwanuddin, Ikhwanuddin (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to determine the mapping of the development and direction of research on Islamic Religious Education in Adolescent Association. In publications indexed by the scopus database. This study used bibliometric analysis techniques to explore all publications indexed in the Scopus database on Islamic Education and Muslim Personality from 1966 to 2023. The data obtained were analyzed using excel and R/R-Studio. VOSviewer is used to perform visual analysis of keyword occurrence and document citations in a stimulating manner. Researchers found 6,224 publications that fit the function, subject, and criteria set. The results of this study show an annual growth rate. The papers are analyzed in terms of publications by field of science, the number of studies published annually. The bibliometric analysis performed was limited to scopus data. Other national and international databases were not taken into account in the study. The limitation of this study is only taking data sets or meta data in publications indexed by Scopus. This study presents a brief overview of the literature accessible to researchers working in the field of Islamic religion and provides recommendations for future research.